From economic integration to socioeconomic inclusion: day labor worker centers as social intermediaries. Issue 2 (7th February 2017) - Visser, M. Anne; Theodore, Nik; Melendez, Edwin J.; Valenzuela, Abel
ABSTRACT: Day labor worker centers have emerged as an important mode of regulatory action in the informal economy of major US cities. Research suggests that these organizations are beneficial in improving employment outcomes experienced by migrant workers engaged in this labor market sector. Yet, the extent to which these organizations impact the social integration of this working population remains relatively undeveloped in the literature. Using data from the National Day Labor Survey, we examine the impact of day labor worker centers on the level of social inclusion experienced by migrant day laborers. We find that worker centers have a modest, but statistically significant, impact on the levels of social integration experienced by this working population and that this varies from city to city. Ultimately we argue that the social intermediary role of these organizations may offer a type of counter mobilization necessary to promote the socioeconomic integration of this working population, but that issues of capacity remain.